2007
DOI: 10.1164/rccm.200705-664oc
|View full text |Cite
|
Sign up to set email alerts
|

Cystic Fibrosis Pulmonary Guidelines

Abstract: It is hoped that the guidelines provided in this article will facilitate the appropriate application of these treatments to improve and extend the lives of all individuals with cystic fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
256
0
21

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 798 publications
(278 citation statements)
references
References 93 publications
1
256
0
21
Order By: Relevance
“…This UK CF registry analysis found that many people with CF do not use any airway clearance techniques, or use exercise as their primary airway clearance technique despite the fact that this is not recommended [2,3]. Forced expiratory techniques and airway clearance devices (PEP and oscillating PEP) were found to be the most common primary airway clearance techniques used by people with CF in the UK, while postural drainage and high-frequency chest wall oscillation are the least common techniques (used by 4% and 1%, respectively).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This UK CF registry analysis found that many people with CF do not use any airway clearance techniques, or use exercise as their primary airway clearance technique despite the fact that this is not recommended [2,3]. Forced expiratory techniques and airway clearance devices (PEP and oscillating PEP) were found to be the most common primary airway clearance techniques used by people with CF in the UK, while postural drainage and high-frequency chest wall oscillation are the least common techniques (used by 4% and 1%, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…Chest physiotherapy to remove airway secretions is recommended by various CF organisations as a vital treatment for people with CF [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…5F) while depriving the EPEC or STEC bacteria of their meal. Indeed, inhaled DNase (dornase) has been shown to improve outcomes of infection in cystic fibrosis patients (33,34), and intrapleural injection of DNase plus a fibrinolytic agent improved recovery from empyema of the chest (35). It is very plausible, therefore, that DNA NETs in the gut lumen may assist EPEC and STEC more than they hurt them and that the role of NETs in vivo may not be as simple as depicted in studies of neutrophils forming NETs on glass microscope slides.…”
Section: Discussionmentioning
confidence: 99%